Analisis Kejenuhan Belajar Siswa Pada Pembelajaran Bahasa Arab Di Madrasah Aliyah Nurul Anwar Padomasan - Elda Roini; Fina Aunul Kafi (STIQ Amuntai, 2026)
Student boredom in Arabic language learning is a problem that leads to low participation and learning effectiveness, influenced by internal factors such as motivation, self-confidence, and language anxiety, as well as external factors such as teaching methods and the classroom environment. This study aims to analyze student participation and the factors causing boredom in Arabic language learning. This study employs a qualitative approach using field research conducted at MA Nurul Anwar Padomasan, involving 10 students from grades 10–12 and 1 Arabic language teacher. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing, with triangulation. The results indicate that student participation is evident but uneven, with students from Islamic boarding schools tending to be more active than those from other schools. Internal factors such as low self-confidence and language anxiety affect student engagement, while external factors, including monotonous lecture methods, an unproductive classroom environment, and the difficulty level of the material, are the primary causes of boredom. The use of interactive methods such as discussions, vocabulary games, dialogue, and icebreakers has proven effective in increasing student participation. Therefore, varied, interactive, and contextual learning strategies are needed to reduce.